An EOQ Model for Phase Inventory with Induced Demand and Periodic Cycle Time. (16th September 2014) - Kumar De, Sujit; Sana, Shib Sankar; Goswami, Adrijit
Abstract : This paper deals with a stock flow of an inventory problem over induced demand. The inventory is consumed through "core customer" or chain marketing system in an induced environment (inductance) to exhaust all the items of the stock inventory in an indefinite time. The demand rate is depicted due to induced factor which is generated from the same inventory presented nearby. The inventory cycle time is split into several periodic times due to oscillatory feature of the inventory which is called phase inventory. Considering uniform demand, this cycle time splits into two basic parts, namely, "first shift" (phase) and "second shift" (phase). Since the process dampens over time, so the whole inventory will exhaust after few periods. A cost function consisted of inventory cost, setup cost, and loss for induced items is minimized to obtain optimal order quantity and replenishment time. The multivariate lagrange interpolation (MLI) over the average values of the postsensitivity analysis is developed here. Finally, graphical illustrations are made to justify the model.